Examining Habitability of Kepler Exoplanets - Kalambokidis, Maria (Proceedings of the Wisconsin Space Conference, 2017)
Since its launch in 2009, the Kepler spacecraft has confirmed the existence of 3,387 exoplanets with the goal of finding habitable environments beyond our own. The mechanism capable of stabilizing a planet’s climate is the long-term carbon cycle driven by plate tectonics. We determined the likelihood of plate tectonics for Kepler exoplanets by comparing their interior structures to planets within our solar system. We used the mineral physics toolkit BurnMan to create three models with the same composition as Earth, Mars, and Mercury. We ran 19 exoplanets through the models and calculated their Mantle Radius Fraction (MRF). We found that four exoplanets may be Chthonian, four have Mercury-like MRF values, and two are Earth-like in their MRF values but did not lie within their habitable zone. In the future, as more exoplanet masses are obtained, it is likely that a greater number will appear dynamically similar to the Earth.